Microstructure Parameter Estimation in Permeability Calculation of Well Cement during Early Hydration by a Simple Particle Expansion Model - Syahrir Ridha , Syahrir (2011)
Abstract— The inter-connected pores of cement after displaced into wellbore is believed to contribute for fluids migration. It cannot be accurately evaluated using the present sonic and acoustic methods due to its density based principles. Impedance technique is applied at elevated temperature and pressure for its pores characterization. A simple particle expansion model is proposed to solve the microstructural parameters (surface and volume of pores) in the unsetting cement that was previously encountered. The proposed model is validated by comparing the trend lines of cement prior to (our model) and after (measurement) setting. The results are employed in the Katz-Thompson equation for estimating its permeability. A comparable result of permeability calculation to the measured data is fairly observed.